An Insight into the Combat Strategies for the Treatment of Type 2 Diabetes Mellitus - Chawla, Gita; Pradhan, Tathagata; Gupta, Ojasvi (Mini Reviews in Medicinal Chemistry, 2024)
Diabetes is a chronic, and metabolic disorder that has gained epidemic proportions in the past few decades creating a threat throughout the globe. It is characterized by increased glucose levels that may be due to immune-mediated disorders (T1DM), insulin resistance or inability to produce sufficient insulin by β-pancreatic cells (T2DM), gestational, or an increasingly sedentary lifestyle. The progression of the disease is marked by several pathological changes in the body like nephropathy, retinopathy, and various cardiovascular complications. Treatment options for T1DM are majorly focused on insulin replacement therapy. While T2DM is generally treated through oral hypoglycemics that include metformin, sulfonylureas, thiazolidinediones, meglitinides, incretins, SGLT-2 inhibitors, and amylin antagonists. Multidrug therapy is often recommended when patients are found incompliant with the first-line therapy. Despite the considerable therapeutic benefits of these oral hypoglycemics, there lie greater side effects (weight variation, upset stomach, skin rashes, and risk of hepatic disease), and limitations including short half-life, frequent dosing, and differential bioavailability which inspires the researchers to pursue novel drug targets and small molecules having promising clinical efficacy posing minimum side-effects. This review summarizes some of the current emerging novel approaches along with the conventional drug targets to treat type 2 diabetes.
Keywords: T2DM